Tidsfæstelse af Grauballemanden ved kulstof-14 måling - Tauber, Henrik (Kuml, 1956)
Dating of Grauballe Man by Carbon-14 Measurement Shortly after excavation of Grauballe Man, and before conservation commenced, parts of the muscle and liver tissue were removed and sent to the Carbon-14 Dating Laboratory in Copenhagen for investigation. The investigation showed a content of 81,5 % Carbon-14 as compared with that of modem material. This is equivalent to an age for Grauballe Man of 1640 ± 140 years. The inaccuracy can be reduced on evaluation of all the measurements of modem carbon and of the background performed in the laboratory, and the final result is a date for the death of Grauballe Man as 310 AD ± 100 years. Repeated measurements could reduce the error still further, but those already made are sufficient to place Grauballe Man without any doubt in the Roman Iron Age. Henrik Tauber